Dramatherapy : the nature of interruption - Hougham, Richard; Jones, Bryn (Dramatherapist) (Routledge, 2021)
"This book investigates the nature and phenomena of interruption in ways, which have relevance for contemporary dramatherapy practice. It is a timely contribution amidst an 'Age of Interruption' and examines how dramatherapists might respond with agency and discernment in personal, professional, and cultural contexts. The writing gathers fresh ideas on how to conceptualise and utilize interruptions artistically, socially, and politically. Individual chapters destabilise traditional conceptions of verbal and behavioural models of psychotherapy and offer a new vision based in the arts and philosophy. There are examples of interruption in practice contexts, augmented by extracts from case studies and clinical vignettes. The book is not a sequential narrative - rather a bricolage of ideas, which create intersections between aesthetics, language, and the imagination. New and international voices in dramatherapy emerge to generate a radical immanence; from Greek shadow puppetry to the Japanese horticultural practice of Shakkei; from the appearance of 'ghosts' in the consulting room to images in the third space of the therapeutic encounter, interruptions are reckoned with as relevant and generative. This book will be of interest to students, arts therapists, scholars, and practitioners, who are concerned with the nature of interruption and how dramatherapy can offer a means of active engagement"--